Constructing proton-conductive highways within an ionomer membrane by embedding sulfonated polymer brush modified graphene oxide - Zhao, L.; Li, Y.; Zhang, H.; Wu, W.; Liu, Jian; Wang, J. (Elsevier SA, 2015)
© 2015 Elsevier B.V. All rights reserved. Abstract Sulfonated polymer brush modified graphene oxide (SP-GO) fillers with controllable brush length are synthesized via the facile distillation-precipitation polymerization, and then incorporated into sulfonated poly(ether ether ketone) (SPEEK) matrix to fabricate composite membranes. The influences of SP-GO upon the microstructures, including thermal and mechanical properties, water uptake/swelling, proton conduction, H2 permeability and single PEMFC performances of composite membranes are intensively investigated. It is found that the SP-GO fillers are uniformly dispersed and tend to lie perpendicularly to the cross-section surface of the whole membrane, which allow SP-GO fillers creating inter-connected and broad ionic pathways through the sulfonic acid groups in polymer brushes. Meanwhile, the SP-GO fillers connect the ionic clusters in SPEEK matrix via interfacial interactions. In such a way, proton-transfer highways are constructed along the SPEEK/SP-GO interface, which lower the proton transfer activation energy and enhance the proton conductivities of the composite membranes under both hydrated and anhydrous conditions. Furthermore, elevating the brush length on SP-GO could further enhance the proton conductivity. Compared to SPEEK control membrane, a 95.5% increase in hydrated conductivity, an 178% increase in anhydrous conductivity and a 37% increase in maximum power density are obtained for the optimal composite membrane.